An evaluation of year four Sekolah Jenis Kebangsaan English textbook / Loh Leh Kwong - Loh, Leh Kwong (2012)
This study evaluates an English textbook entitled Year Four [Sekolah Jenis Kebangsaan (Cina/Tamil)] English Textbook. It is used nationwide by all the Malaysian government funded Chinese primary schools. Five common elements i.e. objectives, contents, vocabulary, grammar and exercises were studied in this research. The presence of the elements of Bloom’s taxonomy were also compared and reviewed against the exercises of the textbook. Teachers and Year 6 students, being the direct users of the textbook were chosen to participate in the study. Questionnaires and interviews were used to collect relevant data. Generally, the textbook complied with most of the objectives set in the curriculum specifications, a guideline determined by the Education Ministry. However, in a world fast moving towards modern era of digital technology, the students showed their thirst for knowledge in new innovations now and then. Teachers also see the need to cater to this request so that the learning of English will be interesting. To determine whether effective learning has taken place, a central assessment of summative examination after six years of primary schooling, is set up by the Malaysian Ministry of Education. It is known as Ujian Penilaian Sekolah Rendah (UPSR). In evaluating the role played by the textbook in the preparation for the examination, the study revealed certain strengths and weaknesses in above-named elements: objectives, contents, vocabulary, grammar and exercises. In the effort to improve the textbook, some suggestions from the participants are put forward. It is hoped that the authorities concerned would find them useful especially at the dawn of reviewing the syllabus and revamping the textbook for future use.